2010
DOI: 10.58886/jfi.v8i1.2350
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Banks and the Global Financial Crisis of 2007-09: An Assessment

Abstract: We examine the experience of the Islamic banks with respect to the global financial crisis of 2007-09 (GFC) and find that these were not immune from the ravages of the GFC. In particular, our analysis of the banking sector in Malaysia shows that the Islamic banks were adversely affected by it to a greater extend then were the conventional banks. Post-December 2008, the capital adequacy ratios for these banks were significantly lower, the loan loss ratios significantly higher, and their total loss reserves and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The easing of monetary policy leads to lower bank financing during the crisis. Therefore, the result obtained is consistent with Uppal and Mangla (2010) indicating that the Islamic banks in the country were not immune from the ravages of the global financial crisis. One of the reasons that might contribute to this finding is due to the Islamic bank financing which is still relying on interest rate as monetary policy indicator.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The easing of monetary policy leads to lower bank financing during the crisis. Therefore, the result obtained is consistent with Uppal and Mangla (2010) indicating that the Islamic banks in the country were not immune from the ravages of the global financial crisis. One of the reasons that might contribute to this finding is due to the Islamic bank financing which is still relying on interest rate as monetary policy indicator.…”
Section: Resultssupporting
confidence: 86%
“…In parallel with other studies, Zuriyati and Roziani (2014) found that GFC has not affected the bank financing in Islamic banks. Nonetheless, Uppal and Mangla (2010) reveal a contrary result. They examined the experience of Islamic banks of two countries (Pakistan and Malaysia) and found that the Islamic banks in the country "were not immune from the ravages of the global financial crisis" to the financial crisis.…”
Section: Literature Reviewmentioning
confidence: 85%
“…According to their findings, Islamic funds show a clear preference for small caps. Uppal and Mangla (2010) provides empirical evidence that the view that Islamic banks are inherently safe is not sustainable in the light of their experience during the Great Financial Crisis (GFC). Additionally, Uppal and Mangla (2010) shows that the actual lending practices of Islamic banks are predominantly based on mark-ups, thus implicitly carry interest.…”
Section: Failure To Develop Risk Sharing Productsmentioning
confidence: 99%
“…Uppal and Mangla (2010) provides empirical evidence that the view that Islamic banks are inherently safe is not sustainable in the light of their experience during the Great Financial Crisis (GFC). Additionally, Uppal and Mangla (2010) shows that the actual lending practices of Islamic banks are predominantly based on mark-ups, thus implicitly carry interest. The study finds that the Islamic banking industry seems to have fallen short of the Islamic ideals, and their practices have moved away in substance from their brand-image towards a convergence to the conventional banking.…”
Section: Failure To Develop Risk Sharing Productsmentioning
confidence: 99%
“…These risks came to surface in the aftermath of the Global Financial Crisis. It has been shown that not only the Islamic banks were not immune from the ravages of the GFC, but were also adversely affected by it to a greater extent than were the conventional banks; Uppal and Mangla (2010b). Though, IBs were not directly impacted by the GFC in its initial phase, the banks experienced the after-shocks of the GFC transmitted through indirect channels.…”
Section: Post Gfc Challenges and Strategic Implicationsmentioning
confidence: 99%